Service-Logic Business Model Canvas in Healthy-Food Industry using Text Mining Approach as Value Co-Creation - Kresna Audito; Andreas Chandra Santoso; Marine Novita; Lamhot Henry Pasaribu (Institute of Computer Science (IOCS), 2022)
Indonesian market, in general, has swift their perception of healthy food much more positively, It is diverting the focus of contact in business relationships towards the coordination of logistical operations that offer value to the client. By applying value co-creation, the Healthy-food industry is anticipated to expedite the process of innovation and invention. In addition, the purpose of this study is to investigate the blueprint for cooperation and creativity utilizing a business model canvas based on service-dominant logic. This initial business model canvas is proposed to offer a qualitative overview of the process of value co-creation (i.e., literature review, observation). It is anticipated that more research will validate the created BMC by giving various statistical evaluations.